2013
DOI: 10.3945/ajcn.112.042606
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal absorption by segmental reversal of the small bowel in adult patients with short-bowel syndrome: a case-control study

Abstract: SRSB allows a gain in macronutrient absorption, which is associated with a lower HPN dependence. To our view, SRSB should be integrated in intestinal rehabilitative adult programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…IEC LEPR‐B‐WT and ‐KO mice were fed an ND or HFD for 3 wk, and indirect calorimetric measurements of whole energy expenditure, oxygen consumption and carbon dioxide production, respiratory exchange rate, food intake, and locomotor activity were performed using calorimetric cages with food and water (Labmaster; TSE Systems, Bad Homburg, Germany), as described previously (26). The stools were collected for determination of excreted fats and total energy by the method of Van de Kamer and bomb calorimetry (PARR 1351 bomb calorimeter; Parr Instrument Co., Moline, IL, USA) as described previously (27, 28).…”
Section: Methodsmentioning
confidence: 99%
“…IEC LEPR‐B‐WT and ‐KO mice were fed an ND or HFD for 3 wk, and indirect calorimetric measurements of whole energy expenditure, oxygen consumption and carbon dioxide production, respiratory exchange rate, food intake, and locomotor activity were performed using calorimetric cages with food and water (Labmaster; TSE Systems, Bad Homburg, Germany), as described previously (26). The stools were collected for determination of excreted fats and total energy by the method of Van de Kamer and bomb calorimetry (PARR 1351 bomb calorimeter; Parr Instrument Co., Moline, IL, USA) as described previously (27, 28).…”
Section: Methodsmentioning
confidence: 99%
“…A recent case-control study of 17 adult SBS patients who had undergone the reversed intestinal segment procedure found that the surgery resulted in a gain in macronutrient absorption and was associated with a lower parenteral nutrition dependence [22]. The same group also recently reported that in 38 adult SBS patients with a reversed jejunal segment of 10-12 cm, 45% of patients had been weaned from parenteral nutrition after 5 years of follow-up, whereas the remainder had reduced their parenteral nutrition requirements from 7 to 4 days/ week [23].…”
Section: Autologous Gastrointestinal Reconstructionmentioning
confidence: 98%
“…Ancak, 2012 ve 2013 yılında bir grup erişkin kısa bağırsak hastasında bu operasyonların etkinliği geniş bir şekilde çalışmış ve ortaya koymuştur (39,40) .…”
Section: B Anizoperistaltik Ince Bağırsak/izoperistaltik Jejunal Veyunclassified